2019
DOI: 10.1097/mlr.0000000000001260
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 2 Forms of Practice Facilitation on Cardiovascular Prevention in Primary Care

Abstract: Background: Effective quality improvement (QI) strategies are needed for small practices. Objective: The objective of this study was to compare practice facilitation implementing point-of-care (POC) QI strategies alone versus facilitation implementing point-of-care plus population management (POC+PM) strategies on preventive cardiovascular care. Design: Two arm, practice-randomized, comparative effectiveness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…Advancements in innovative treatments like thrombolytic treatment, balloon angioplasty, laser therapy, and arterectomy have improved the medical management of cardiovascular patients (Persell et al, 2020). However, cardiac surgery (CS) is still the mainline treatment for many patients with CVDs.…”
mentioning
confidence: 99%
“…Advancements in innovative treatments like thrombolytic treatment, balloon angioplasty, laser therapy, and arterectomy have improved the medical management of cardiovascular patients (Persell et al, 2020). However, cardiac surgery (CS) is still the mainline treatment for many patients with CVDs.…”
mentioning
confidence: 99%
“…While a previously published assessment of our study [29] found no association between the overall duration of the practice facilitation, as measured by number of minutes or number of visits, and overall study clinical quality measure outcomes (e.g., improvement in the Million Hearts ABCS clinical quality measures), we saw a distinct association between number and duration of visits with practice groups that participated in more coaching and completed more QI interventions, consistent with the systematic review of facilitation activities performed by Baskerville et al [8]. Likewise, practices that participated in more activities under the Project Management and Coaching strategy categories were more likely to complete the study.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, compared to baseline measures of the CQMs in the 226 participating practices, we saw a modest increase in all four measures after year-long practice facilitation support: 4% increases in aspirin use for ischemic vascular disease and controlling high blood pressure, and 5% increases in statin therapy for prevention and treatment of cardiovascular disease and tobacco use (smoking) screening and cessation. All increases were significant (p < 0.001), and importantly, improvements were sustained at 18 months, when facilitation had been absent for 6 months [29]. However, CQMs are a measure of practice-and patient-level outcomes while practice facilitators focus on supporting implementation of specific QI interventions to effect long-term practice change.…”
Section: Contributions To the Literaturementioning
confidence: 96%
See 1 more Smart Citation
“…Practices in the POC+PM arm reported an average of 6 visits from their practice facilitator over the implementation period and an average of 2 remote contacts. 31 In prior implementations, 21,23,32 CommunityRx integrated with EMR platforms to auto-generate the HealtheRx. Due to variation in H3 practices' EMR platforms, availability, and use, and barriers to execution of institutional agreements, the H3 implementation of CommunityRx was not integrated with practices' EMRs.…”
Section: Interventionmentioning
confidence: 99%